A structural model of alcohol consumption among high school students - Aguilar Villalobos, Javier (Consorcio de Universidades Mexicanas A.C., 2014)
The objective of this study was to develop and test a structural model of drinking among high school students based on the results of a similar study with college students, and to analyze the differences between the results of both investigations. In a sample of 190 high school students were applied the following scales: motives for drinking (compliance, coping and social-improvement), negative expectations, problems, drinking friends, attending parties, sensation seeking and three consumption measures, which were developed and / or adapted in the undergraduate study. Subsequently, scales were validated by multiple regression analysis and a structural model of drinking was developed, which showed a good fit to the data according to accepted indexes. The resulting model showed that alcohol consumption was directly affected by the above reasons, negative expectations and assistance to parties, and indirectly by sensation seeking and drinking friends. The most notable differences between high school and undergraduate are the greatest resistance to consumer pressure group in high school and greater awareness of the risks of drinking among college students.